Geometric Design and Prototyping of a (2-RRU)-URR Parallel Mechanism for Thumb Rehabilitation Therapy - Woo-hyeok Choi; Yukio Takeda (Machines, 2021)
In this paper, the geometrical design of a (2-RRU)-URR (where R and U stand for the revolute and universal joints, respectively) parallel mechanism was demonstrated for thumb rehabilitation therapy. This paper consists of two parts: the design procedure for the development of a thumb rehabilitation device and the user experiment with the prototype. Because the hand generally has a limited working area, the design of the hand attachment parts and the placement of the actuators requires careful consideration of the various factors. Along with the kinematic requirements of the device, the interaction between the mechanism and the fingers must be considered. The proposed mechanism has three actuators placed in the hand attachment. When the mechanism is attached to the hand, there is the possibility of collisions between the fingers of the user and the mechanism. Two design candidates were devised while considering the limited working area of the hand and the need to avoid collisions. Due to the dependency of the workspace on the placement of the actuators, a comparison of the workspace of the two candidate designs and the target workspace was carried out. The target workspace was determined through the use of thumb trajectory measurement data. A prototype was manufactured using 3D printed plastic and aluminum materials. To confirm the practical performance of the prototype, user experiments were conducted in which a comparison between the thumb measurement data and the controlled trajectory of each person was done. Motion in two directions, specifically, adduction–abduction and flexion–extension were performed. The results showed that the controlled trajectory of flexion–extension were closely matched to the thumb measurement trajectory. Finally, the experimental results are discussed.